COVID-19 news a way to promote statistics classes - Silvestre, Cláudia (2022)
Artigo baseado na comunicação proferida no ICERI2021-14th annual International Conference of Education, Research and Innovation, (virtual conference), Seville, Spain, 08-10 novembro 2021